Emerging market financial services development: the case of leasing in Poland and China. (1st January 2014) - Jaworski, Piotr Marek; Gao, Simon; Sliwinski, Adam
The aim of this paper is to present Polish and Chinese developments in this area in the period of 1999–2009 for the former and 2005–2008 the latter and then to compare both markets for 2007 and 2008 using different metrics. The time horizon is limited due to the lack of Chinese data. The results show that both economies used leasing to finance ongoing business and both markets have many common features. The results show also that although the Chinese leasing market is less developed, it catches up with the more developed Polish counterpart.